Sports participation and adiposity do not mediate the relationship between birth weight and arterial thickness in adolescents: ABCD Growth Study. (May 2019) - Urban, Jacqueline; Cayres, Suziane; Codogno, Jamile; Turi-Lynch, Bruna; Mantovani, Alessandra; Fernandes, Romulo
Abstract: Objective: To analyse the relationship of altered birth weight with metabolic and cardiovascular outcomes among adolescents, as well as to identify if sports participation is able to attenuate or even eliminate the impact of birth weight on health outcomes. Methods: Cross-sectional study (Analysis of Behaviours of Children During Growth [ABCD Growth Study]). Adolescents with age ranging from 11 to 18 years old (14.7±2.1) stratified according to normal (n = 230) and altered (n = 35) birth weight composed the sample. Birth weight was self-reported by adolescent's parents. Sports participation was assessed by face-to-face interview. Carotid intima–media thickness (CIMT) and femoral intima–media thickness (FIMT) were measured using an ultrasound device. C-reactive protein levels were used to assess the inflammatory status. Blood pressure, Z score of metabolic risk (dyslipidemia and glucose), adiposity, and insulin resistance were covariates. Results: In the crude model, FIMT (p value = 0.037) and C-reactive protein (p value = 0.029) were affected by altered birth weight. In the adjusted models, altered birth weight affected FIMT (p value = 0.048; small effect size of 1.7%), independently of sports participation. For C-reactive protein, previous time of engagement in sports (p value = 0.001; small effect size of 4.8%) affected C-reactive protein, independently of birth weight. Conclusion: Vascular structure seems to be affected by birth weight in adolescents, while its impact on inflammation seems to be attenuated by the regular engagement in sports.